Decision-making management procedures. - Johannesen, Odma (Nordic Council Of Ministers, 2014)
This study report analyses the strengths and weaknesses of the procedures which are followed when designating marine Natura 2000 sites and when deciding what fisheries management measures are to be applied. The report identifies weaknesses in the current system and proposes to replace the existing procedures with a single-stringed system structuring the national and international processes in a single regional integrated environmental-fisheries process. This process should include extensive stakeholder involvement.